PERAN KULINER ASING TERHADAP PERKEMBANGAN INDUSTRI KATERING DI INDONESIA - Alifa Fitria (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2025)
This study looks into how foreign cuisine is shaping the catering industry in Indonesia and highlights the essential role of local traditions in keeping our national identity alive. We used a qualitative research approach, conducting interviews and observations with catering business owners and customers to gain insights into how globalization affects our food choices and practices. Our findings reveal that while foreign dishes can make catering services more appealing and boost sales, local food still holds a special place in the hearts of consumers because of its rich flavors and cultural significance. Catering businesses that mix exciting foreign culinary trends with distinctive local tastes are the ones that thrive in today’s competitive market. This blend not only helps them stay sustainable and profitable but also plays a vital role in preserving Indonesia’s diverse cultural heritage. By embracing and honoring local traditions, these businesses can celebrate our national identity while adapting to the ever-changing food scene.